Social Interaction Patterns in Inclusive Education of Elementary School (Journal of Primary Education, 2019)
The objective of this study is to determine the form of patterns of social interaction in inclusive education at Public Elementary School Sudirman Ambarawa. The method of this research was qualitative. The focus of the study examined the social interactions that occurred between Children with Special Needs with their peers, normal students, teachers, principals in forming patterns of social interaction. The research subjects were eight Children with Special Needs in the III grade and IV grade, four normal students in the III grade and IV grade of Public Elementary School Sudirman Ambarawa. The technique of collecting data used in-depth interviews, observations, and documentation. The validity technique of this research data used triangulation method and source triangulation. Data analysis techniques used the interactive analysis model of Miles and Huberman. The results of this study indicate that the pattern of social interaction in elementary school takes place in harmony. It is obtained from the efforts of the teacher to instill the value of tolerance, cooperation, and respect for students who are guided by Vygotsky's social learning theory. Previously, it conducted the identification of social interaction aspects based on Blummer's symbolic interactionism theory and George Homans's social exchange theory. So that it can be concluded that a pattern of harmonious social interaction is formed in Public Elementary School Sudirman Ambarawa, referring to a circle pattern that shows the freedom of each member to relate to any party in their group.